Visualization of oxidative stress in ex vivo biopsies using electron paramagnetic resonance imaging. Issue 4 (18th April 2014) - Gustafsson, Håkan; Hallbeck, Martin; Lindgren, Mikael; Kolbun, Natallia; Jonson, Maria; Engström, Maria; de Muinck, Ebo; Zachrisson, Helene
Abstract : Purpose: The purpose of this study was to develop an X‐Band electron paramagnetic resonance imaging protocol for visualization of oxidative stress in biopsies. Methods: The developed electron paramagnetic resonance imaging protocol was based on spin trapping with the cyclic hydroxylamine spin probe 1‐hydroxy‐3‐methoxycarbonyl‐2, 2, 5, 5‐tetramethylpyrrolidine and X‐Band EPR imaging. Computer software was developed for deconvolution and back‐projection of the EPR image. A phantom containing radicals of known spatial characteristic was used for evaluation of the developed protocol. As a demonstration of the technique electron paramagnetic resonance imaging of oxidative stress was performed in six sections of atherosclerotic plaques. Histopathological analyses were performed on adjoining sections. Results: The developed computer software for deconvolution and back‐projection of the EPR images could accurately reproduce the shape of a phantom of known spatial distribution of radicals. The developed protocol could successfully be used to image oxidative stress in six sections of the three ex vivo atherosclerotic plaques. Conclusions: We have shown that oxidative stress can be imaged using a combination of spin trapping with the cyclic hydroxylamine spin probe cyclic hydroxylamine spin probe 1‐hydroxy‐3‐methoxycarbonyl‐2, 2, 5, 5‐tetramethylpyrrolidine and X‐Band EPR imaging. A thorough and systematic evaluation on different types of biopsies must be performed in the future to validate the proposed technique.Magn Reson Med 73:1682–1691, 2015. © 2014 Wiley Periodicals, Inc.